How they got it and how they wanted it: Marginalised young people's perspective on their experiences of sexual health education - Brown, Graham; Sorenson, Anne; Hildebrand, Janina (Sex Education, 2012)
Young people in Australia are at greatest risk of contracting sexually transmitted infections, and priority actions are necessary for this population group. This study of marginalised and at-risk young people in out-of-school environments was conducted in Western Australia with the aim of obtaining young people's perceptions about their experience of sexual health education and preferred means of gaining sexual health knowledge and skills. A participatory research methodology was implemented through a series of workshops with 88 young people recruited through community youth agencies. The results of the study support what is already known about sexual health promotion for young people and the importance of a holistic approach to promoting positive relationships and sexual health. However, the findings emphasise that this should include the need for demonstrated trust, confidence and safe environments, and the complementary role of community youth agencies and peer-based programmes which may play an important role in reaching young people who may disengage with, or not be reached by school-based sexual health education.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; australie; discipline; personnes marginalisées; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle